2016
DOI: 10.1111/ddi.12461
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the historical distribution of sturgeons (Acipenseridae) in the eastern North Atlantic based on ancientDNAand bone morphology of archaeological remains: implications for conservation and restoration programmes

Abstract: Aim In the 19th/early 20th century, overfishing caused a drastic decline and finally extinction of the local sturgeon populations in the eastern Atlantic. To date, it is not known whether it was Acipenser sturio or the primarily North American Acipenser oxyrinchus that occurred here. The aim of the study was to show the historical pattern of sturgeon distribution and their diversity in this area over the last 2500 years. This question is essential for international restoration programmes. Location North‐east A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Notwithstanding the use of a recently developed extraction protocol aimed to maximize endogenous DNA (54), this rate of success compares favorably to results from mammalian bones whereby the majority of samples-excluding petrous bonestypically yield a few percent endogenous DNA at most (55). Our positive results agree with studies using PCR-based methods that have reported successful amplification from fish bones (56)(57)(58)(59)(60) in some cases up to 10,000 y old (61). The observation that porous, light fish bones can yield whole genome shotgun libraries with high levels of endogenous DNA underscores our lack of understanding of DNA preservation in different types of animal bone.…”
Section: Discussionsupporting
confidence: 78%
“…Notwithstanding the use of a recently developed extraction protocol aimed to maximize endogenous DNA (54), this rate of success compares favorably to results from mammalian bones whereby the majority of samples-excluding petrous bonestypically yield a few percent endogenous DNA at most (55). Our positive results agree with studies using PCR-based methods that have reported successful amplification from fish bones (56)(57)(58)(59)(60) in some cases up to 10,000 y old (61). The observation that porous, light fish bones can yield whole genome shotgun libraries with high levels of endogenous DNA underscores our lack of understanding of DNA preservation in different types of animal bone.…”
Section: Discussionsupporting
confidence: 78%
“…Genetic and archeological evidence shows that AS originating from northern North American colonized the Baltic Sea approximately 1200 years ago, flourished, and were exploited by humans until fished out (Ludwig et al., , ; Ludwig and Gessner, ). Additional evidence of further AS excursions to Europe and apparent hybridization with the European Sturgeon has recently been reported (Chassaing et al., ; Nikulina and Schmölcke, ). Records from Bermuda and French Guiana suggest additional trans‐oceanic migrations.…”
Section: Distribution Abundance Mortality and Population Trendsmentioning
confidence: 65%
“…For example, both archaeological and historical data show temporal changes (major reductions) in the distribution of anadromous fishes such as sturgeons Acipenser spp. and salmon Salmo salar L. 1758 in the rivers around the North Sea (Desse‐Berset, ; Lenders et al, ; Nikulina & Schmölcke, ; Thieren et al, ). In the case of Acipenser spp., comparison of past and present further demonstrates that both Acipenser sturio L. 1758 and Acipenser oxyrinchus Mitchill 1815 once occupied European waters.…”
Section: Biogeographymentioning
confidence: 99%
“…In overcoming these challenges (Nicholson, 2000;Nims & Butler, 2018), we are cautiously learning more about the environmental (pre) history of sea fishing in Europe and globally, yielding insights that are of direct relevance to sustainable fisheries today. This paper aims to provide a brief overview of the potential for archaeological analyses to inform our understanding of: Lenders et al, 2016;Nikulina & Schmölcke, 2016;Thieren et al, 2016). In the case of Acipenser spp., comparison of past and present further demonstrates that both Acipenser sturio L. 1758 and Acipenser oxyrinchus Mitchill 1815 once occupied European waters.…”
Section: Introductionmentioning
confidence: 99%